(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND: Heart transplantation remains the most durable treatment for patients with end-stage heart failure refractory to medical treatment. Central elements of the listing criteria for heart transplantation have remained largely unchanged in the last three decades whereas treatment of heart failure has significantly increased survival and reduced disease-related symptoms. It remains unknown whether the improvement of heart failure therapy changed the profile of heart transplantation candidates or affected post-transplant survival. METHODS: The study investigated a total of 323 heart transplant recipients of the Lausanne University Hospital with 328 transplant operations between 1987 and 2018. Patients were separated into three groups on the basis of availability of heart failure therapy: period 1 (1987–1998; n = 115) when renin-angiotensin system blockade and diuretic treatment were available; period 2 (1999–2010; n = 106) marked by the addition of beta-blocker and mineralocorticoid receptor antagonist treatment in severe heart failure, and the establishment of cardiac defibrillator and resynchronisation therapy; period 3 (2011–2018; n = 107) characterised by the increasing use of ventricular assist devices for bridge to transplantation. RESULTS: The patient characteristics age (all: 53.4 years), male sex (all: 79%) and body mass index (all: 24.5 kg/m2) did not differ between periods. History of arterial hypertension was less prevalent in period 2 (period 1 vs 2 vs 3: 44 vs 28 vs 43%, p = 0.04) whereas other cardiovascular risk factors were equally distributed. Left ventricular ejection fraction, VO2max, and pulmonary vascular resistance were not different between the three periods. The prevalence of ischaemic cardiomyopathy was higher in periods 1 and 3; dilated non-ischaemic cardiomyopathy was more frequent in period 2. Post-transplant 1-year survival was highest in period 3 (1 vs 2 vs 3: 87.2 ± 3.2% vs 70.8 ± 4.4% vs 93.0 ± 2.6%, p always ≤0.02), and the Kaplan-Meier estimates of survivors of the first year post-transplant were not different between the three periods. In descriptive analysis, early mortality was not associated with acknowledged pretransplant predictors of post-transplant mortality. CONCLUSION: Availability of different medical heart failure treatments did not result in greatly different pretransplant characteristics of heart transplantation recipients across the three periods. This suggests that the maintained central criteria of listing for heart transplantation still identify end-stage heart failure patients with a similar profile. This finding can explain the unchanged overall mortality on condition of 1-year survival across the three periods, since pretransplant characteristics are relevant for long-term survival after heart transplantation.